High-efficiency ultrafast Tm-doped fiber amplifier based on resonant pumping - Jin, Xiaoxi (2019)
We demonstrated a high-efficiency ultrafast Tm-doped fiber amplifier based on a resonant pumping technique. A continuous-wave fiber laser at 1940 nm was employed as the pump laser. The slope efficiency of the resonantly pumped pulsed Tm-doped fiber amplifier reached 87% with respect to the launched pump power. The maximum average output power reached 40 W when the launched pump power was 53 W. The repetition rate and the pulse duration of the output pulses from a fiber amplifier were 248 MHz and 129 ps, respectively. The corresponding peak power was 1.25 kW, and the pulse energy was 161.3 nJ. To the best of our knowledge, this is the first demonstration of a resonant pumping enabled high-power high-efficiency ultrafast fiber laser operating at a 2 μm band.